2018
DOI: 10.1007/s10971-018-4778-8
|View full text |Cite
|
Sign up to set email alerts
|

From sol–gel prepared porous silica to monolithic porous Mg2Si/MgO composite materials

Abstract: Mg 2 Si is apart from its conductivity properties expected to be a promising candidate for thermoelectric applications due to its low toxicity, low costs, and the high abundance of its precursor chemicals. Through the addition of a homogeneous distribution of nanoparticles (e.g. MgO) and by reducing the size of Mg 2 Si to the nanometer regime, it is possible to decrease the thermal conductivity by increasing phonon-interface scattering and, as a result, improve the thermoelectric properties. However, classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…11 In addition, Elsaesser and co-workers reported that porous Mg 2 Si can be prepared by Mg vapor annealing of a silica monolith comprising rod-like silica particles. 12,13 These reports indicate that porous Mg 2 Si can be synthesized by forming porous silica followed by Mg vapor treatment. However, granular composites exhibit reduced conductivity because of the contact resistance between particles.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, Elsaesser and co-workers reported that porous Mg 2 Si can be prepared by Mg vapor annealing of a silica monolith comprising rod-like silica particles. 12,13 These reports indicate that porous Mg 2 Si can be synthesized by forming porous silica followed by Mg vapor treatment. However, granular composites exhibit reduced conductivity because of the contact resistance between particles.…”
Section: Introductionmentioning
confidence: 99%
“…3) Mg 2 Si-based composites were also investigated for thermoelectric applications. [4][5][6][7][8][9] The Mg 2 Si/Si composites for thermoelectric applications were investigated due to their decreasing thermal conductivity by effective phonon scattering at the grain boundaries. [10][11][12] In addition, the Mg 2 Si/Si composite is also expected to be an anode material in Li ion batteries and its high capacity characteristics were reported.…”
Section: Introductionmentioning
confidence: 99%